A Preliminary Study on Integrating Procedural Content Generation into Game Development Process - Pratama Wirya Atmaja; Rizky Parlika; Sugiarto (IJCONSIST JOURNALS, 2019)
Abstract— Digital game industry continues to grow and reap enormous profit. On the other hand, game development is still a risky and costly endeavor, and researches on reducing its risks and costs continue to be important. Procedural content generation or PCG is the state-of-the-art method to speed up and automate the production of various game contents, therefore reducing the said costs and risks. However, how to integrate the method into the lengthy process of game development is still not well understood. In this paper we present a preliminary study on the integration. For the development process, we combine MDA or Mechanics-Dynamics-Aesthetics framework with SCRUM-based Agile methodology. The PCG method for our study is for generating levels of platformer games. We study how the PCG method would be developed in pre-production and production phases with the help of two common development tools, Game Design Document (GDD) and user stories. We discuss our findings and possible directions of future researches.